A Novel Method for Vibrotactile Proprioceptive Feedback Using Spatial Encoding and Gaussian Interpolation - Marinelli, A.; Boccardo, N.; Canepa, M.; Domenico, D. Di; Semprini, M.; Chiappalone, M.; Laffranchi, M.; De Michieli, L.; Dosen, S. (IEEE transactions on biomedical engineering, 2023)
Objective: The bidirectional communication between the user and the prosthesis is an important requirement when developing prosthetic hands. Proprioceptive feedback is fundamental to perceiving prosthesis movement without the need for constant visual attention. We propose a novel solution to encode wrist rotation using a vibromotor array and Gaussian interpolation of vibration intensity. The approach generates tactile sensation that smoothly rotates around the forearm congruently with prosthetic wrist rotation. The performance of this scheme was systematically assessed for a range of parameter values (number of motors and Gaussian standard deviation). Methods: Fifteen able-bodied subjects and one individual with congenital limb deficiency used vibrational feedback to control the virtual hand in the target-achievement test. Performance was assessed by end-point error and efficiency as well as subjective impressions. Results: The results showed a preference for smooth feedback and a higher number of motors (8 and 6 versus 4). With 8 and 6 motors, the standard deviation, determining the sensation spread and continuity, could be modulated through a broad range of values (0.1 - 2) without a significant performance loss (error: ∼ 10%; efficiency: ∼ 30%). For low values of standard deviation (0.1-0.5), the number of motors could be reduced to 4 without a significant performance decrease. Conclusion: The study demonstrated that the developed strategy provided meaningful rotation feedback. Moreover, the Gaussian standard deviation can be used as an independent parameter to encode an additional feedback variable. Significance: The proposed method is a flexible and effective approach to providing proprioceptive feedback while adjusting the trade-off between sensation quality and the number of vibromotors.